2021
DOI: 10.1080/08870446.2021.1890730
|View full text |Cite
|
Sign up to set email alerts
|

The Aussie-FIT process evaluation: feasibility and acceptability of a weight loss intervention for men, delivered in Australian Football League settings

Abstract: EQ, NN, CTN, KH, CG, RUN, DFG, SW, PJM, DAK, and SR conceived the project and obtained the project funding. EQ, DK, CD, CTN, KH, CG contributed to the development of the interview guides and conducted the data analysis reported in this manuscript. DK, JO, EQ and CD recruited participants. CD conducted all interviews. HB conducted coding of audio-recorded data. MM and DK contributed to data processing and interpretation. EQ and DK wrote the first draft of the manuscript. All authors contributed to the refinemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Our results also add to the literature by providing a New Zealand and rugby union perspective and adding weight to the importance of the characteristics of the coach delivering the programme, the communication and presentation skills of those delivering the education sessions, and the efforts that should be encouraged to create a team-based environment. Interestingly, the importance of the franchise involvement for continued engagement did not come across as strongly as in previous research e.g., [ 17 , 21 ].…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Our results also add to the literature by providing a New Zealand and rugby union perspective and adding weight to the importance of the characteristics of the coach delivering the programme, the communication and presentation skills of those delivering the education sessions, and the efforts that should be encouraged to create a team-based environment. Interestingly, the importance of the franchise involvement for continued engagement did not come across as strongly as in previous research e.g., [ 17 , 21 ].…”
Section: Discussionmentioning
confidence: 45%
“…Our results illustrated that engagement with the programme was heavily influenced by: (1) factors brought to the programme by the men who enrolled: their life situations, motivations and behaviours, and how those factors supported the creation of a team atmosphere; (2) the supportive, motivating and skilful coach who delivered the programme; and (3) factors inherent to the design and content of the programme: the knowledge gained from the education sessions and its situation within professional sport. Although the results may appear similar to those from evaluations of other ‘Fans in Training’ style lifestyle programmes [ 17 , 18 , 19 , 20 , 21 ], these programmes are all conducted slightly differently (for example, RuFIT-NZ used dieticians to deliver nutrition content, strength and conditioning coaches to deliver the main programme content), hence there is a need to understand participant experiences of each. Our results also add to the literature by providing a New Zealand and rugby union perspective and adding weight to the importance of the characteristics of the coach delivering the programme, the communication and presentation skills of those delivering the education sessions, and the efforts that should be encouraged to create a team-based environment.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, in the gender tailored Australian Football themed Aussie‐Fans in Training program, 426 men registered their interest in participating within 3 days of advertising 35 . Despite the clear program appeal, the authors reported limited sample diversity in terms of socioeconomic status and ethnicity 35,105 . In the FFIT RCT in Scotland, without specific targeting of recruitment efforts beyond the location of professional football clubs known to attract people from a wide range of socioeconomic backgrounds in their fan base, the program recruited men from across the socioeconomic spectrum 26 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 Despite the clear program appeal, the authors reported limited sample diversity in terms of socioeconomic status and ethnicity. 35 , 105 In the FFIT RCT in Scotland, without specific targeting of recruitment efforts beyond the location of professional football clubs known to attract people from a wide range of socioeconomic backgrounds in their fan base, the program recruited men from across the socioeconomic spectrum. 26 Gender‐tailoring and aligning interventions with men's interests can engage men who would not otherwise participate; however, depending on the context, specific targeting (e.g., in lower socioeconomic areas or regional towns) and tailoring (e.g., for specific ethnic groups) may be required to reach more diverse populations more representative of the burden of obesity‐related disease.…”
Section: Discussionmentioning
confidence: 99%